Uji Kepekaan Obat Anti Tuberkulosis Lini Kedua Menggunakan BACTEC Mycobacterium Growth Indicator Tubes (MGIT) 960 - Rukminiati, Yuni (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2012)
The emergence of Multidrug resistance tuberculosis (MDR TB) is a failure treatment caused by Mycobacterium tuberculosis is real threat for TB control program. Second line drugs were using for person who has MDR TB. The objective of this study was to evaluate the Mycobacterium Growth Indicator Tube (MGIT) 960 System as media for testing of Mycobacterium tuberculosis susceptibility to second line drugs. Levels of high sensitivity and specificity, and time of the testing time is the parameter being assessed. Thirty MDR TB isolates were tested for susceptibility to ofloxacin, amikacin, and kanamycin by MGIT 960, and the result were compared to those obtain with proportion method on Lowenstein Jensen media, considered a reference method. Results for ofloxacin showed sensitivity 100% and specificity 75%, whereas for amikacin sensitivity 96% and specificity 100%; kanamycin sensitivity showed both specificity of 100%. The time required to obtain result was faster compared to the reference method, with an average of 9 days by the MGIT960